Visualized simulation design for cyber-physical systems based on the supervisory control framework - Wang, Qiushi (Nanyang Technological University, 2023)
Industry 4.0 aims to use computer technology to assist industrial production and is helpful in improving the performance of industrial systems in all aspects. This project focuses on product delivery systems. The contribution of this paper is twofold; firstly, it illustrates a method for modelling and controlling flexible manufacturing systems; secondly, it provides an optimisation algorithm based on solver constraint solving. The first part of the Project is to build a production line simulation model using simulation software, simulate real production scenarios by selecting suitable components, imitate the activities of the production line by establishing signal connections, and use external software for supervision. In addition, the optimization of the model is also a part of the concern. The solver can be used to optimize the scheduling of production, not only for systems using conveyor delivery, but also for AGV systems. Keywords: Industry 4.0, AGVs system simulation, Optimization.